Loss of the mammalian G-protein coupled receptor, G2A, modulates severity of invasive pulmonary aspergillosis - Steffan, Breanne N.; Calise, Dante; Park, Sung Chul; Niu, Mengyao; Yang, Jun; Hammock, Bruce D.; Jones, MaryJane; Steele, Chad; Keller, Nancy P. (Frontiers in Immunology, 2023)
Background Aspergillus fumigatus is a well-known opportunistic pathogen that causes a range of diseases including the often-fatal disease, invasive pulmonary aspergillosis (IPA), in immunocompromised populations. The severity of IPA is dependent on both host- and pathogen-derived signaling molecules that mediate host immunity and fungal growth. Oxylipins are bioactive oxygenated fatty acids known to influence host immune response and Aspergillus developmental programs. Aspergillus synthesizes 8-HODE and 5,8-diHODE that have structural similarities to 9-HODE and 13-HODE, which are known ligands of the host G-protein-coupled receptor G2A (GPR132). Materials and methods Oxylipins were extracted from infected lung tissue to assess fungal oxylipin production and the Pathhunter β-arrestin assay was used to assess agonist and antagonist activity by fungal oxylipins on G2A. An immunocompetent model of A. fumigatus infection was used to assess changes in survival and immune responses for G2A-/- mice. Results Here we report that Aspergillus oxylipins are produced in lung tissue of infected mice and in vitro ligand assays suggest 8-HODE is a G2A agonist and 5,8-diHODE is a partial antagonist. To address the hypothesis that G2A could be involved in the progression of IPA, we assessed the response of G2A-/- mice to A. fumigatus infection. G2A-/- mice showed a survival advantage over wild-type mice; this was accompanied by increased recruitment of G2A-/- neutrophils and increased levels of inflammatory markers in A. fumigatus-infected lungs. Conclusions We conclude that G2A suppresses host inflammatory responses to Aspergillus fumigatus although it remains unclear if fungal oxylipins are involved in G2A activities.